Graficzny obraz systemu prawa: prawo, estetyka, estetyka prawa? - Zajadło, Jerzy (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
Legal philosophy is concentrated on such traditional philosophical problems like ontology, epistemology, logic and ethics. Obviously it lacks the last main philosophical issue — aesthetics. The author tries to fill this gap with so-called pragmatic aesthetics formulated by R. Schusterman. Using the latin terminology he claims that the law should be not only certa, praevia, scripta et stricta, but pulchra as well. On this background the author proposes two graphic models of the legal system: the first, concentrated on the logical structure e.g. H. Kelsen, H.L.A. Hart, and the second, concentrated on the axiological borders e.g. G. Radbruch, L.L. Fuller. In the conclusion he presents also some new proposals, like for example three-dimensional vision of the global law formulated by R. Domingo.
Keywords: legal philosophy; pragmatic aesthetics; Schusterman, Richard; Hart, Herbert L.A. (1907-1992); global law